Self-assembling CuS anodes with conversion reaction for ultrafast Na-ion storage - Kim, Sung Yeob; Ahn, Hee-Jae; Kim, Young-Hoon; Kim, Hong-Kyu; Lee, Byeong-Hyeon; Byeon, Young-Woon; Park, Jae-Ho; Chung, Kyung Yoon; Lee, Jae-Chul (Royal Society of Chemistry, 2023)
Battery anodes with high capacity, fast-charging capability, and long cycling stability are crucial for the development of next-generation energy storage devices. Current approaches to achieve these properties often involve the use of expensive nanoscale materials or complex modification techniques. This study presents a microsized CuS conversion anode for Na-ion batteries that provides a simple and cost-effective solution to this challenge. Utilizing the distinct attributes of the Na-CuS system, which allows microscale bulk CuS particles to spontaneously convert to a porous nanostructure and prompts the emergence of conductive Cu nanoparticle networks through the conversion reaction, our study highlights exceptional electrochemical performance of the CuS anode. The developed anode provides a large capacity of 546 mA h g-1 at 10C, remarkable cyclability of 4325 cycles at 10C, and excellent rate performance of 500 mA h g-1 at 30C, which are among the best reported properties for conversion anodes. The results of utilizing the microsized untreated CuS conversion anode present a novel methodology for developing high-performance battery electrodes without the need for costly materials or complicated synthesis methods. Our study provides insights into the physical mechanisms underlying the superior electrochemical performance of the CuS anode, and its potential as a high-performance, low-cost conversion anode material for next-generation energy storage devices. Our results offer new avenues for scalable, affordable energy storage solutions, with potential applications across various industries. The CuS anode enables spontaneous transformation into a porous nanostructure and the formation of conductive Cu nanoparticles. These features of the CuS conversion anode for Na-ion batteries exhibit remarkable electrochemical performance.